Model Kehadiran Kristiani Berbasis Kebajikan: Trialog Teks Surat kepada Murid Diognetus, James Davison Hunter dan Eka Darmaputera sebagai Imajinasi Baru Tri-Tugas Gereja - Junaedi, Ujun (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2023)
This article is an intertextual reading of three models of Christian presence from three texts, namely The Epistle to Diognetus, an extra-canonical text of the second century; the text To Change the World by James Davison Hunter, an American sociologist; and the views of Eka Darmaputera, an Indonesian theologian. The findings of the three texts are analyzed using Alasdair MacIntyre’s concept of virtue, which rejuvenates Aristotle’s idea of virtue ethics. Through intertextual analysis of these three texts, the findings related to Christian presence are used to construct a model of virtue-based Christian presence. This virtue-based model of Christian presence is used as the basis for building an image of the three-duties model of the church, namely koinonia, diakonia, and marturia. This effort aims to answer the struggle of balancing the model of church presence between internal and external factors.